Developing an Educational Logic Programming Game for High School Students Using C++ - Arif Surachman; Muhammad Singgih Zulfikar Ansori; Miftakhus Surur (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Computational thinking and logic programming are essential skills in the 21st-century curriculum, yet many high school students find traditional syntax-based learning daunting. This research aims to develop an educational game designed to teach logic programming concepts to high school students using the C++ language. The development follows the Game Development Life Cycle (GDLC), incorporating phases from initiation to release. The game focuses on algorithmic problem-solving, control structures, and logical operators through an interactive, gamified interface. Evaluation using the Technology Acceptance Model (TAM) indicates high levels of perceived usefulness and ease of use among students. The results suggest that gamification significantly lowers the cognitive barrier to entry for C++ programming, fostering a more engaging learning environment for novice programmers.